Hybrid Renewable Energy System with High Gain Modified Z-Source Boost Converter for Grid-Tied Applications - Sathish Ch.; Chidambaram I.A.; Manikandan M. (Problems of the Regional Energetics, 2023)
In a hybrid renewable system, a conventional boost converter produces more losses at the time of the energy conversion process due to this, the performance of the hybrid system is reduced total harmonic distortion is increased, and the hybrid microgrid outcome is reduced. The main objective of the work enhancing the low DC voltage produced by the PV panel, a high gain Boost converter is utilized. The objectives of the work were achieved by a High Gain Modified Z-source Boost converter along with Modified Particle Swarm Optimized- Proportional Integral (MPSO-PI) controller employed in the energy conversion stage at Grid. It reduced power conversion stages and decreases the losses compared to existing Hybrid Grid-connected systems. A new 13-bus system is developed in this work for regulating the output voltage in distribution networks. The significance of our work lies in the design of an efficient microgrid system for grid-tied applications. High Gain Modified Z-source Boost converter along with Modified Particle Swarm Optimized- Proportional Integral (MPSO-PI) controller is employed to boost the voltage obtained from the PV system. A battery converter along with a bi-directional battery is connected to the DC link, to store energy generated by Hybrid Renewable Energy System (HRES) in excess amounts. The obtained DC link voltage is transferred to Three Phase VSI for the conversion of DC to AC voltage. Effective harmonic reduction is attained with the aid of an LC filter coupled to Three Phase grid, and the PI controller connected to Voltage Source Inverter(VSI) supports achieving effective grid synchronization. The proposed work was tested with 13 bus system through MATLAB Simulink.